Characterization and antivirus activities of a novel bovine IFN-omega24. Issue 2 (August 2015) - Luo, Xiuxin; Guo, Yongli; Bao, Jun; Liu, Ying; An, Dong; Ma, Bo; Gao, Mingchun; Wang, Junwei
Highlights A novel bovine IFN-ω subtype gene was amplified and named BoIFN-ω24. The recombinant mature peptide was expressed in prokaryotic expression system. BoIFN-ω24 has antiviral activity on MDBK, BT and PK-15 cells. Physicochemical characteristics and antiproliferation of BoIFN-ω24 were determined.